Anti-Semitism pada Penafsiran M. Quraish Shihab terhadap ayat-ayat tentang Yahudi dalam Tafsir al-Misbah - Hamdan, Ali; Mahmudi, Zaenul; Muhammad, Muhammad (Institut Agama Islam Negeri (IAIN) Curup, 2023)
Anti-Semitism in M. Quraish Shihab's Interpretation of verses about Jews in Tafsir al-MisbahThis article aims to analyze more deeply the issue of anti-Semitism in the interpretation of the Qur'an Quraish Shibah. Seeing the growing movement of adherents of the Jewish religion in Indonesia and the emergence of a survey from the Wahid Foundation that Indonesian Muslims do not like Judaism, it is necessary to have an in-depth study regarding the interpretation of Indonesian figures towards Jewish verses in the Koran. Quraish Shihab apart from being an intellectual figure in Indonesia who has a complete commentary of 30 chapters, he is also one of Indonesia's political figures. Quraish Shihab's interpretation of Judaism needs to be explored to track and analyze more deeply whether there are elements of anti-Semitism in his interpretation, seeing that he is one of the intellectual and political figures of Indonesian Muslims. To reveal the interpretation of Quraish Shihab, the descriptive-analytical method is the guideline in this article. After carrying out the analysis, it was found that Tafsir al-Misbah still has a strong impression of anti-Semitism, although it does not apply equally to all adherents of the Jewish religion. Regarding the characteristics revealed by Quraish in describing the Jews, namely: often playing against each other, jealous, and often committing lies, and aspiring for Muslims to embrace Judaism